Research Trends in Digital Financial Inclusion: A Bibliometric Analysis using VOSviewer - Ahiase, Godwin; Umar, Abdurrauf; Marwan. M. Saeed, Abdulmalek; Abedin Rasuman, Mohammad; Rianti do Rego Tilman Suri, Epifania (Universitas Komputer Indonesia, 2024)
Digital financial inclusion (DFI) aims to provide affordable and sustainable financial services to financially excluded and underserved populations through cost-saving digital means. The purpose of the study is to conduct a bibliometric analysis of DFI using VOSviewer software. A bibliometric and descriptive quantitative approach was employed. Data was collected based on the keyword